Disparities in Obstetric Readmissions: A Multistate Analysis, 2007–2014 - Matthews, Kathy C.; Tangel, Virginia E.; Abramovitz, Sharon E.; Riley, Laura E.; White, Robert S. (American Journal of Perinatology, 2021)
Objective Hospital readmissions are generally higher among racial-ethnic minorities and patients of lower socioeconomic status. However, this has not been widely studied in obstetrics. The aim of the study is to determine 30-day postpartum readmission rates by patient-level social determinants of health: race ethnicity, primary insurance payer, and median income, independently and as effect modifiers.Study Design Using state inpatient databases from the health care cost and utilization project from 2007 to 2014, we queried all deliveries. To produce accurate estimates of the effects of parturients' social determinants of health on readmission odds while controlling for confounders, generalized linear mixed models (GLMMs) were used. Additional models were generated with interaction terms to highlight any associations and their effect on the outcome. Adjusted odds ratios (aOR) with 95% confidence intervals are reported.Results There were 5,129,867 deliveries with 79,260 (1.5%) 30-day readmissions. Of these, 947 (1.2%) were missing race ethnicity. Black and Hispanic patients were more likely to be readmitted within 30 days of delivery, as compared with White patients (p < 0.001 and p < 0.05, respectively). Patients with government insurance were more likely to be readmitted than those with private insurance (p < 0.001). Patients living in the second quartile of median income were also more likely to be readmitted than those living in other quartiles (p < 0.05). Using GLMMs, we observed that Black patients with Medicare were significantly more likely to get readmitted as compared with White patients with private insurance (aOR 2.78, 95% CI 2.50–3.09, p < 0.001). Similarly, Black patients living in the fourth (richest) quartile of median income were more likely to get readmitted, even when compared with White patients living in the first (poorest) quartile of median income (aOR 1.48, 95% CI 1.40–1.57, p < 0.001).Conclusion Significant racial-ethnic disparities in obstetric readmissions were observed, particularly in Black patients with government insurance and even in Black patients living in the richest quartile of median income.Key Points
Keywords: delivery; ethnicity; obstetric; race; race ethnicity; readmission; social determinants of health